Good citizens, perfect patients, and family reputation: Stigma and prolonged isolation in people with drug-resistant tuberculosis in Vietnam - Lisa Redwood; Greg J. Fox; Thu Anh Nguyen; Sarah Bernarys; Paul Mason; Van Anh Vu; Viet Nhung Nguyen; Ellen M. H. Mitchell (Public Library of Science (PLoS), 2022)
Stigma and isolation are common in people with tuberculosis (TB). Social isolation contributes to reduced health outcomes and TB treatment adherence. Stigma and the drivers of isolation in people with Drug-Resistant (DR)-TB may include modifiable advice and practices of family and Health Care Workers (HCW). This study aimed to understand the drivers of isolation and stigma from the perspective of people with DR-TB in Vietnam. A greater understanding of stigma and isolation is important to identify and balance patients' needs and disease transmission risk. In-depth interviews were conducted with 12 people with DR-TB and seven HCWs who care for people with DR-TB in two provinces in Vietnam. Interviews were audio-recorded, transcribed verbatim and translated to English. Data collection and analysis were conducted simultaneously. The data were then analysed using a thematic framework approach. Stigma and extended isolation were common experiences among people with DR-TB. To mitigate stigma, people with DR-TB used the local term 'lao lực' to describe their condition to others which is believed to be a less infectious and less stigmatising type of TB. This study identified that although HCW informed people with DR-TB of when they were no longer infectious and isolation was no longer required, their infection control advice was not always consistent. Despite knowing they were no longer infectious, most people with DR-TB continued to self-isolate to minimise the perceived repercussions of societal stigma, to protect their 'thể diện' (honour, prestige, reputation), and eliminate all risk of transmitting DR-TB to their family. This study identified three interconnected drivers of self-isolation in Vietnam, including fear of infecting others, fear of stigmatization, and to protect family reputation. TB control programmes need to better understand the social aspects of DR-TB to enable them to better support patients. Educating HCW to provide evidence-based infection control advice is vital.